DESKRIPSI PENGGUNAAN MIND MAP PADA MATA KULIAH ILMU GIZI - Wita Ferwati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2018)
The purpose of this research is to now: (1) describing the use of mind map in nutritional science courses (2) describing the activities in learning process. Research methods used is descriptive method. The populations is student were taking courses in nutritional science of July to December 2018. The sample is the entire population totaling 15 people. data collection technique is interviews, observation and documentation. Data processed deskriptif. The results showed that the mind map can be increase student learning activities including: a) increased student activity in expressing opinions from 49% increased to 64%, b) increased ability in explaining from 51% to 72%, c) presenting discussion results from 53% to 69%, d) commenting and responding in discussions the group increased from 49% to 72%, e) corrected errors / shortcomings in the discussion process increased from 53% to 75%, f) concluded the subject matter with his own opinion increased from 48% to 76%, and from the results of interviews with